Hubungan Toxic Parenting terhadap Perilaku Emosional Anak Usia Dini - Ramadani, Nur; Agusniatih, Andi; Amrullah, Amrullah; Durrotunnisa, Durrotunnisa (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to determine the relationship between toxic parenting and the emotional behavior of early childhood in Group B of TK Alkhairaat 1 Kaleke, Dolo Barat District, Sigi Regency. This study employed a quantitative approach with a correlational design. The research subjects consisted of 15 children and their parents, selected using a total sampling technique. Data were collected through questionnaires and observations of children's emotional behavior, which included aspects of independence, self-confidence, and helping behavior toward peers. Data analysis was conducted using the Pearson Product Moment correlation test. The results showed that the correlation coefficient was 0.552 with a significance value of 0.033 (< 0.05), indicating a significant relationship between toxic parenting and children's emotional behavior. The level of correlation was categorized as moderate. In addition, observational results indicated an improvement in children's emotional behavior from the first week to the second week, influenced by adaptation processes and stimulation from the school environment. Based on these findings, it can be concluded that toxic parenting is significantly related to the emotional behavior of early childhood. Therefore, parents are encouraged to apply positive parenting styles to support optimal emotional development in children.